Carcinogenic effect of human tumor-derived cell-free filtrates in nude mice - Berlanga-Acosta, Jorge; Arteaga-Hernandez, Ernesto; Garcia-Ojalvo, Ariana; Duvergel-Calderin, Dayanis; Rodriguez-Touseiro, Marisol; Lopez-Marin, Laura; Suarez-Alba, Jose; Fuentes-Morales, Dasha; Mendoza-Fuentes, Osmany; Fernández-Puentes, Sheyla; Nuñez-Figueredo, Yanier; Guillen-Nieto, Gerardo (Frontiers in Molecular Biosciences, 2024)
Cancer remains as a worldwide cause of morbidity and mortality. Investigational research efforts have included the administration of tumors-derived extracts to healthy animals. Having previously demonstrated that administration of non-transmissible, human cancers-derived homogenates induced malignant tumors in mice; we examined here the consequences of administering 50 or 100 µg of protein of crude homogenates from mammary carcinoma, pancreatic adenocarcinoma, and melanoma samples in six inoculations per week during two months. Concurrent control received homogenates of healthy donor-skin cosmetic surgery fragments. Mammary carcinoma homogenate administration did not provoke animals’ deterioration or mortality. Multiple foci of lung adenocarcinomas with broad expression of malignity histomarkers, coexisting with small cell-like carcinomas were found. Disseminated cells, positive to classic epithelial markers were detected in lymphoid nodes. Pancreas tumor and melanoma homogenates administrations progressively deteriorated animals’ health. Pancreas tumor induced lung poorly-differentiated adenocarcinomas and pancreatic islets hyperplasia. Melanoma affected lungs with solid pseudopapillary adenocarcinomas. Giant atypical hepatocytes were also observed. Kidney exhibited dispersed foci of neoplastic cells within a desmoplastic matrix. A noticeable nuclear overlapping with hyperchromatic nuclei, mitotic figures, and prominent nuclear atypia was identified in epidermal cells. None of these changes were ever detected in control mice. Furthermore, incubation of zebrafish embryos with breast tumors homogenate induced the expression of c-Myc and HER-2 as tumor markers, contrasting to embryos exposed to healthy tissue-derived material. This study confirms and extends our hypothesis that tumor homogenates contain and may act as vector for “malignancy drivers”, which ultimately implement a carcinogenesis process in otherwise healthy mice.